2019
DOI: 10.3389/fmicb.2019.00881
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Potential and Safety Evaluation of Enterococcus faecalis OB14 and OB15, Isolated From Traditional Tunisian Testouri Cheese and Rigouta, Using Physiological and Genomic Analysis

Abstract: Lactic acid bacteria (LAB) strains OB14 and OB15 were isolated from traditional Tunisian fermented dairy products, Testouri cheese and Rigouta, respectively. They were identified as Enterococcus faecalis by the MALDI TOF-MS (matrix assisted laser desorption-ionization time of flight mass spectrometry) biotyper system and molecular assays (species-specific PCR). These new isolates were evaluated for probiotic properties, compared to E. faecalis Symbioflor 1 clone DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 90 publications
(106 reference statements)
4
73
0
Order By: Relevance
“…Four E. faecalis strains were used in this study, two pathogenic strains: MMH594 ( Huycke et al, 1991 ) and V583 ( Sahm et al, 1989 ), isolated from blood, and two probiotic strains: OB15 isolated from Rigouta, a Tunisian traditional fermented dairy product ( Baccouri et al, 2019 ) and Symbioflor 1 DSM 16431 isolated from a stool specimen of an healthy human adult (Symbiopharm, Herborn, Germany). Bacteria were routinely grown at 37°C under static conditions in brain heart infusion (BHI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four E. faecalis strains were used in this study, two pathogenic strains: MMH594 ( Huycke et al, 1991 ) and V583 ( Sahm et al, 1989 ), isolated from blood, and two probiotic strains: OB15 isolated from Rigouta, a Tunisian traditional fermented dairy product ( Baccouri et al, 2019 ) and Symbioflor 1 DSM 16431 isolated from a stool specimen of an healthy human adult (Symbiopharm, Herborn, Germany). Bacteria were routinely grown at 37°C under static conditions in brain heart infusion (BHI).…”
Section: Methodsmentioning
confidence: 99%
“…In this context, the aim of our work was to evaluate the effect of the catecholamine stress hormones, epinephrine (Epi), and norepinephrine (NE) on some Enterococcus s trains. Four E. faecalis strains were included in this study: E. faecalis MMH594 and E. faecalis V583, pathogenic strains of clinical origin, E. faecalis Symbioflor 1 clone DSM 16431, a pharmaceutical probiotic, and E. faecalis OB15, a probiotic strain previously isolated from Tunisian rigouta ( Baccouri et al, 2019 ). Epi was found to modulate the formation of biofilm (biovolume and thickness) in E. faecalis , whether pathogens or probiotics.…”
mentioning
confidence: 99%
“…Recently, we isolated E. faecalis OB15 from rigouta, a popular traditional Tunisian fermented cheese that is often prepared by boiling acidified cheese whey from cow’s milk ( 7 ). Physiological and genomic analyses demonstrated that E. faecalis OB15 has met all of the principle requirements for and has properties of an efficient probiotic and could be a reliable candidate for future use in the food or feed industry ( 7 ).…”
Section: Announcementmentioning
confidence: 99%
“…Several strains are known to be opportunistic pathogens and are recognized among the major etiological agents of nosocomial and other human infections (endocarditis and urinary tract infections), due to their ability to acquire resistance to a wide range of antibiotics and the presence of virulence determinants (2, 3). In contrast, other strains have potential benefits for human health and are currently used as starter cultures in manufacturing cheese (4, 5), as bacteriocin (enterocins) producers in food preservation, and as potential probiotics in the food industry (1, 6).Recently, we isolated E. faecalis OB15 from rigouta, a popular traditional Tunisian fermented cheese that is often prepared by boiling acidified cheese whey from cow's milk (7). Physiological and genomic analyses demonstrated that E. faecalis OB15 has met all of the principle requirements for and has properties of an efficient probiotic and could be a reliable candidate for future use in the food or feed industry (7).Genomic DNA of E. faecalis OB15 was extracted from an overnight culture in MRS broth at 37°C, under static conditions, with the GeneJET genomic DNA purification kit (Thermo Fisher Scientific, France), following the manufacturer's recommendations.…”
mentioning
confidence: 99%
“…In addition, they produce bile salt hydrolases and are resistant to low pH, and are therefore able to stay alive until they reach the intestinal tract. However, these two Gram-positive lactic acid bacteria have been implicated in infectious diseases and a careful examination of antibiotic susceptibility, virulence, and absence of hemolysis and cytotoxicity is required before their use as starters and possibly probiotics [8][9][10].…”
mentioning
confidence: 99%